PENGEMBANGAN DASAR-DASAR FILOSOFIS BAGI ILMU PENDIDIKAN - wahyudin wahyudin (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
Science originated from human curiosity of the phenomenon around him or anything about himself. At first the desire to know it is hampered by various myths that developed in the community. The Myths are successfully implanted in the human mind, because of the limitations of the human mind itself to provide and obtain a reasonable explanation. Philosophy and methodology of the study are filling and expanding the horizons of what is called cognitive science, which will hopefully lead to the notion of discipline and scientific work. According to Lakatos elements that should be known in the research program: Hard core, Protective belt and a series theory